'If you're uncomfortable, go outside your comfort zone': A novel behavioral 'stretch' intervention supports the well-being of unhappy people. Issue 3 (4th May 2023) - Russo-Netzer, Pninit; Cohen, Geoffrey L.
ABSTRACT: An increasingly large body of research in social psychology has underscored the power of brief situational interventions in promoting purposeful change. The present research contributes to the literature on positive psychology interventions (PPIs) by testing a novel volitional intervention that encourages people to engage in activities 'outside their comfort zone.' Participants were randomly assigned either to a condition that encouraged them to engage in an activity outside of their comfort zone over the following two weeks or to a control condition that encouraged them to keep a record of their daily activities. The intervention boosted the life satisfaction of people who were relatively less happy at baseline, with exploratory analyses tentatively suggesting benefits strongest among people who went outside their comfort zone by helping others. Discussion centers on the potential of behavioral 'stretch' interventions to promote positive change and well-being among people dissatisfied with their life.